Pola Komunikasi Penyuluh Pertanian Dalam Program Peningkatan Kapasitas Petani Jagung Di Kabupaten Sumbawa (Studi Kasus Kelompok Tani Desa Luk Kecamatan Rhee Kabupaten Sumbawa) - Ade Mula Mulyana; Fahrunnisa Fahrunnisa (KAGANGA KOMUNIKA: Journal of Communication Science, 2021)
This is evident from the fact that Luk Village's petunia corn production has increased in the previous 5 years. In increasing the capacity of farmers this is caused by a communication process carried out by agricultural extension agents with farmer groups. So in this study the researcher intends to find out how the communication patterns of agricultural extension agents in the program to increase the capacity of maize farmers in Sumbawa Regency.This research uses a case study qualitative method. The theoretical analysis used is the SMCRE theory from David Kennet Berlo and the Communication Patterns from Effendy so that farmers can find out the communication process and communication patterns that occur at the agricultural extension agent with the Luk Village farmer groups. The informants of this study were agricultural extension workers and farmer groups in Luk. Collecting data through observation, interviews, and documentation. The results of this study indicate that in the capacity building program there is an SMCR communication process, the SMCR process itself includes:Message source, message, communication channel, message recipient, and finally the communication effect. Then there were 3 communication patterns carried out by the agricultural extension agents in the corn farmer groups of Luk Village including one-way communication patterns, two-way communication patterns, and multidirectional communication patterns Keywords: Communication Patterns, Agricultural Extension, Corn Farmer Group